Enhancing Dynamic Control and Stability Assessment of Cessna 172 Aircraft with a PID Controller for New Pilot Trainees - Dagal, Idriss; Erol, Bilal; Harrison, Ambe; Mbasso, Wulfran Fendzi; Ibrahim, AL-Wesabi (SPRINGER, 2025)
This research proposes a novel approach to enhance the dynamic control and stability assessment of the Cessna 172 aircraft for new pilot trainees by incorporating a proportional-integral-derivative (PID) controller. The PID controller is designed to improve the aircraft's responsiveness to control inputs, reduce overshoot and settling time, and enhance overall stability. The study involves developing a mathematical model of the Cessna 172's longitudinal dynamics, designing a PID controller, and conducting simulations to evaluate the performance of the PID-controlled aircraft. The evaluation focuses on key metrics such as stability, responsiveness, overshoot, and settling time. The results of the study demonstrate that the PID controller effectively enhances the dynamic control and stability of the Cessna 172, providing new pilot trainees with a safer and more efficient learning experience. The PID controller's ability to mitigate the effects of pilot errors and disturbances contributes to improved flight performance and reduced risk of accidents. Future research directions include exploring the use of adaptive PID controllers, integrating PID controllers with other advanced flight control systems, and conducting flight tests to validate the performance of the PID-controlled Cessna 172 in real-world conditions.
Keywords: Aircraft stability; Dynamic control; Pilot training; PID controller; Cessna flight dynamics; Engineering